2014
DOI: 10.1186/1476-7120-12-42
|View full text |Cite
|
Sign up to set email alerts
|

Two and three dimensional echocardiography for pre-operative assessment of mitral valve regurgitation

Abstract: Mitral regurgitation may develop when the leaflets or any other portion of the apparatus becomes abnormal. As the repair techniques for mitral valve disease evolved, so has the need for detailed and accurate imaging of the mitral valve prior to surgery in order to better define the mechanism of valve dysfunction and the severity of regurgitation. In patients with significant mitral valve disease who require surgical intervention, multiplane transesophageal echocardiogram (TEE) is invaluable for surgical planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
1
6
0
1
Order By: Relevance
“…Thus, despite studies revealing validity and utility of ERO and related parameters in a research setting, our study confirms the results showing variable feasibility in a clinical setting . As in the study of Quader et al., we showed that E‐wave velocity was not sensitive enough to exclude severe MR, therefore not useful as a screening tool. Regarding the qualitative measurements, both jet characteristics and SR contributed more to the final score.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, despite studies revealing validity and utility of ERO and related parameters in a research setting, our study confirms the results showing variable feasibility in a clinical setting . As in the study of Quader et al., we showed that E‐wave velocity was not sensitive enough to exclude severe MR, therefore not useful as a screening tool. Regarding the qualitative measurements, both jet characteristics and SR contributed more to the final score.…”
Section: Discussionsupporting
confidence: 76%
“…Some patients with ischemic DCM may develop more focal LV remodeling, such as that following myocardial infarction (MI), and the PMs can therefore be unequally damaged. 21 MV tethering is usually symmetric in patients with global LV dysfunction and remodeling, with increased LV sphericity. The MR jet is central in patients with global wall motion abnormalities, with equal lateral displacement of the PMs, similar to nonischemic cardiomyopathy 21 (Figure 3 might occur in patients with multiple vessel disease and old inferior MI, mainly affecting the posterior PM.…”
Section: Complex Anatomy Of the MVmentioning
confidence: 99%
“…Válvula mitral.-La valoración de la compleja anatomía y función mitral se realiza con imágenes adquiridas en el modo zoom, lo que permite utilizar la máxima resolución temporal y espacial (Quader et al 2014, Buck y Plitch 2015. El mayor avance respecto a las técnicas 2D, es la posibilidad de observar la válvula desde una perspectiva frontal, bien desde el VI o desde la aurícula izquierda (AI).…”
Section: Aplicacionesunclassified